Liechtenstein : Assessment of the Supervision and Regulation of the Financial Sector Technical Note on the Basel Core Principles and IOSCO Securities. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Liechtenstein has a GDP of USD 5.2 billion, of which 40 percent comes from industry and 30 percent from financial services. Currently, 15 banks operate in Liechtenstein (one additional bank is in the process of being wound down without loss to the depositors). The market is highly concentrated with the three largest banks accounting for 90 percent of the total banking balance sheet size; 86 percent of assets under management; 89 percent of operating profits before tax, and 63 percent of employment in the banking sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet